Analysis of volatile compounds of clove (syzygium aromaticum) buds as influenced by growth phase and investigation of antioxidant activity of clove extracts. (7th December 2015) - Kasai, Hiroko; Shirao, Mika; Ikegami‐Kawai, Mayumi
Abstract: The volatile compounds originating from fresh clove ( Syzygium aromaticum ) buds cultivated in a medicinal plant garden located in southern Tokyo were investigated. The volatile compounds originating from fresh clove buds were adsorbed onto polydimethylsiloxane‐coated devices and then analysed using gas chromatography‐mass spectrometry. Sampling was performed at three different development stages of clove buds, i.e., phase I (green), phase II (pink), and phase III (red). In thermal desorption‐gas chromatography‐mass spectrometry procedure volatile compounds: eugenol, β‐caryophyllene, α‐humulene, α‐farnesene, and eugenol acetate were the predominant constituents in most cases. Methyl salicylate, α‐copaene, β‐ocimene, 2‐nonanone, ethyl hexanoate, and acetophenone were additionally found as the buds ripened. Volatile compounds obtained from clove leaves were analysed using the same method, and β‐caryophyllene, eugenol, α‐humulene, 3‐hexen‐1‐ol, 3‐hexen‐1‐yl acetate, and hexyl acetate were identified. The antioxidant activity of both water and methanol extracts of clove buds and leaves collected from the medicinal plant garden was confirmed using electron spin resonance spectrometry. Scavenging activities against superoxide anion radical and hydroxyl radical were evaluated. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The effects of growth phase on volatile compounds originating from fresh clove ( Syzygium aromaticum ) buds were investigated. An increase in the number of volatile compounds as the buds ripened was observed. The antioxidant activity of extracts of clove buds and leaves was confirmed using electron spin resonance spectrometry.